Interleukin-1 Inhibitors and Vaccination Including COVID-19 in Inflammatory Rheumatic Diseases: A Nonsystematic Review - Atagündüz, Pamir; Keser, Gökhan; Soy, Mehmet (Frontiers in Immunology, 2022)
Newly emerging variants of coronavirus 2 (SARS-CoV-2) raises concerns about the spread of the disease, and with the rising case numbers, the Coronavirus disease 2019 (COVID-19) remains a challenging medical emergency towards the end of the year 2021. Swiftly developed novel vaccines aid in the prevention of the spread, and it seems that a specific cure will not be at hand soon. The prognosis of COVID-19 in patients with autoimmune/autoinflammatory rheumatic diseases (AIIRD) is more severe when compared to the otherwise healthy population, and vaccination is essential. Evidence for both the efficacy and safety of COVID-19 vaccination in AIIRD under immunosuppression is accumulating, but the effect of Interleukin-1 on vaccination in general and in AIIRD patients is rarely addressed in the current literature. In light of the current literature, it seems that the level of agreement on the timing of COVID-19 vaccination is moderate in patients using IL-1 blockers, and expert opinions may vary. Generally, it may be recommended that patients under IL-1 blockade can be vaccinated without interrupting the anti-cytokine therapy, especially in patients with ongoing high disease activity to avoid disease relapses. However, in selected cases, after balancing for disease activity and risk of relapses, vaccination may be given seven days after the drug levels have returned to baseline, especially for IL-1 blocking agents with long half-lives such as canakinumab and rilonacept. This may help to ensure an ideal vaccine response in the face of the possibility that AIIRD patients may develop a more pronounced and severe COVID-19 disease course.